Os corpos literários de Guadalupe Nettel - Gonçalves, Karollayne Martins (2023)
The present study intends to promote literary reflections concerning the female body and to investigate how the representation of the body occurs in the contemporary novel O corpo em que nasci (2013), by the Mexican writer Guadalupe Nettel. From bibliographic research, inscribed in the perspective of cultural studies, we seek to understand how the main character's body conception is built taking into consideration the issues that concern the patriarchal culture, the literary tradition, and the written experience from the female point of view. Besides that, this study understands itself as part of the critical reception of a female authorship book and discusses the problems related to women's writings. To achieve the proposed goals, this study is based on, mainly, the critical and theoretical assumptions of Elizabeth Grosz (2000), Teresa de Lauretis (1994), Guacira Lopes Louro (2010), Judith Butler (2010), Gerda Lerner (2019), Helèné Cixous (2017), Adrienne Rich (2017), Norma Telles (1992), Sandra Gilbert e Susan Gubar (2017), Gloria Anzaldúa (2017), Nelly Richard (2002), Édouard Glissant (2021) and Silvia Federici (2017), who present the concepts of female writing, disciplined body, gender performativity, and abjection.